2018
DOI: 10.2147/copd.s156409
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COPD and respiratory symptoms associated with biomass smoke exposure in a suburban area

Abstract: IntroductionBiomass smoke exposure (BSE) is a recognized cause of COPD particularly in rural areas. However, little research has been focused on BSE in suburban areas.ObjectiveThe aim of this study was to determine the prevalence of COPD, respiratory symptoms (RS) and BSE in women living in a suburban area of Mexico City exposed to BSE.MethodsA cross-sectional epidemiological survey of a female population aged >35 years was performed using a multistage cluster sampling strategy. The participants completed ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 31 publications
2
29
1
1
Order By: Relevance
“…Finally, a group of contacts exposed to biomass burning, without a history of active or passive smoking, without evidence of pulmonary disease and normal spirometry values was also included (BBES, n = 183). Participants in this group are part of the national program for equality between women and men with the "Diagnóstico oportuno de EPOC/Respirar sin humo" campaign in women living in rural areas, primarily in the northern highlands of the state of Oaxaca and suburban areas of the Tlalpan mayoralty of Mexico City 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, a group of contacts exposed to biomass burning, without a history of active or passive smoking, without evidence of pulmonary disease and normal spirometry values was also included (BBES, n = 183). Participants in this group are part of the national program for equality between women and men with the "Diagnóstico oportuno de EPOC/Respirar sin humo" campaign in women living in rural areas, primarily in the northern highlands of the state of Oaxaca and suburban areas of the Tlalpan mayoralty of Mexico City 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Cases and controls of biomass-burning exposure are part of the national program for equality between women and men with the "Diagnóstico oportuno de EPOC/Respirar sin humo" campaign in women living in rural areas, mainly in the northern highlands of the state of Oaxaca and suburban [44] areas of the Tlalpan mayoralty of Mexico City. Subjects attending campaigns from 2014 to 2018 were included.…”
Section: Case and Control Groupsmentioning
confidence: 99%
“…However, a range of organic materials (such as coal, animal dung, agricultural waste, and wood) are utilized for cooking and heating purposes in poorly ventilated houses [ 3 ], leading to chronic exposure to smoke from biomass burning. A study conducted in suburban areas near Mexico City observed that nearly 47% of women employ any biomass source for cooking and detected a COPD prevalence of 3% [ 4 ]; previously, the PLATINO study reported a COPD prevalence of 7.8% in Mexico City [ 5 ].…”
Section: Introductionmentioning
confidence: 99%